Multiple low dose therapy as an effective strategy to treat EGFR inhibitor-resistant NSCLC tumours - João M. Fernandes Neto (Nature Portfolio, 2020)
A drug used at the maximum tolerated dose can exert a strong selective pressure on cancer cells leading to resistance. In this study, the authors demonstrate the efficacy of using low dose of multiple drugs for preventing and treating resistance to EGFR tyrosine kinase inhibitors in NSCLC cells.